Motivation of Recovery of Victims of Drugs Using in Rehabilitation at the National Narcotics Agency (BNN) City of Payakumbuh - Rama Anggi Putra; Sri Putri Rahayu Z; Luiz Kenzi; Abdul Ahmad (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2022)
For drug abusers, rehabilitation is essential to do by giving motivating drug abusers to recover and stop using drugs. The study aimed to determine the mottreasone recovery of victims of drug abusers undergoing rehabilitation at the National Narcotics Agency (BNN) Payakumbuh with qualitative research methods. The results showed that the first abuser's motivation to recover was driven by himself (intrinsic motivation) as contained in the motivational aspect of driving, the second family (extrinsic motivation) to direct, then the environment (extrinsic motivation) to support him to recover from drug abuse. Apart from yourself, tbiggestost considerableouragement for abusers to recover is from family or parents. These two things arintendeded, where if one of them has no motivation to recover, then the recovery will not work well